Variety of CSR practices during the covid-19 pandemic - Safakul Fatahullah, Zihad Safakul Fatahullah (COMMICAST, 2022)
This study aims to identify various CSR practices during covid-19, especially CSR practices that focuses on reducing the economic impact on vulnerable communities. The results of this there are various CSR practices carried out by big companies in Indonesia in order to create a culture of shared prosperity through positive interactions with employees, families and communities around the company to improve the quality of life together during the oveid-19 pandemic. Corporate CSR during the pandemic covid-19 has a freat opportunity to bring out the best innovations in making social contributions which mean as a from of long-term development in achieving a balance between profitability and harmony with its various stakeholders. Meanwhile, examples of companies that taken in this study is the practice of CSR carried out by Grab, PT. Pertamina. This matter shows that CSR programs during a pandemic are aimed at vulnerable groups of people.